JUMPING FOR JOY : The History of Platform Video Games - Scullion, Chris (Yorkshire : White Owl an imprint of Pen & Sword Books Limited, 2022)
This platformer is one of the most well-loved video game genres ever, having entertained players for over 40 years. Jumping for joy is a celebration of everything platform games have to offer, spanning their entire history. This book includes platforms starring Mario, Nintendo's mascot and the most popular video game character of all time
Keywords: Video games; Video games -- History